Development of short circuit detection and protection test for three-phase inverter - Goyle, Vakul (2016)
In present day scenario, use of power converter system in applications where safety is critical has become inevitable. This also further increases and enhances the reliability of such systems. Power semiconductor devices such as IGBT’s have become an important component and the failure of these devices can cause catastrophic failure of the entire system. Short circuit faults are one of the most important causes for the failure of the devices. The main objective of this project is to develop a simulation and an experimental setup of a three-phase inverter system to validate the short circuit detection algorithm developed in Rolls-Royce corporate lab @NTU. A Power converter is an electro-mechanical device that converts electrical energy. Primarily the conversion is being done from DC supply to AC supply. A Switch is one of the most important component of converters and inverters as it controls the power of the system. IGBT is one of the main device that is used as a switch for its flexibility and fast switching characteristics. This project gives an insight into the experimental setup and simulation for the detection of short circuit using desaturation mode. Different approaches for short circuit detection have been discussed in the further chapters, introducing the user to new innovative techniques with their solutions for further and future research.